CuZnSOD gene deletion targeted to skeletal muscle leads to loss of contractile force but does not cause muscle atrophy in adult mice. Issue 9 (31st May 2013) - Zhang, Yiqiang; Davis, Carol; Sakellariou, George K.; Shi, Yun; Kayani, Anna C.; Pulliam, Daniel; Bhattacharya, Arunabh; Richardson, Arlan; Jackson, Malcolm J.; McArdle, Anne; Brooks, Susan V.; Van Remmen, Holly
Abstract : We have previously shown that deletion of CuZnSOD in mice ( Sod1 –/– mice) leads to accelerated loss of muscle mass and contractile force during aging. To dissect the relative roles of skeletal muscle and motor neurons in this process, we used a Cre‐Lox targeted approach to establish a skeletal muscle‐specific Sod1‐knockout (mKO) mouse to determine whether muscle‐specific CuZnSOD deletion is sufficient to cause muscle atrophy. Surprisingly, mKO mice maintain muscle masses at or above those of wild‐type control mice up to 18 mo of age. In contrast, maximum isometric specific force measured in gastrocnemius muscle is significantly reduced in the mKO mice. We found no detectable increases in global measures of oxidative stress or ROS production, no reduction in mitochondrial ATP production, and no induction of adaptive stress responses in muscle from mKO mice. However, Akt‐mTOR signaling is elevated and the number of muscle fibers with centrally located nuclei is increased in skeletal muscle from mKO mice, which suggests elevated regenerative pathways. Our data demonstrate that lack of CuZnSOD restricted to skeletal muscle does not lead to muscle atrophy but does cause muscle weakness in adult mice and suggest loss of CuZnSOD may potentiate muscle regenerative pathways.—Zhang, Y., Davis, C., Sakellariou, G.K., Shi, Y., Kayani, A.C., Pulliam, D., Bhattacharya, A., Richardson, A., Jackson, M.J., McArdle, A., Brooks, S.V., Van Remmen, H. CuZnSOD gene deletion targeted to skeletal muscle leads to loss of contractile force but does not cause muscle atrophy in adult mice. FASEB J. 27, 3536–3548 (2013). www.fasebj.org